Implementing Federalism in the Health System of Nepal: Opportunities and Challenges - Rajshree Thapa; Kiran Bam; Pravin Tiwari; Tirtha Kumar Sinha; Sagar Dahal (Kerman University of Medical Sciences, 2019)
Nepal moved from unitary system with a three-level federal system of government. As federalism accelerates, the national health system can also speed up its own decentralization process, reduce disparities in access, and improve health outcomes. The turn towards federalism creates several potential opportunities for the national healthcare system. This is because decision making has been devolved to the federal, provincial and local governments, and so they can make decisions that are more representative of their localised health needs. The major challenge during the transition phase is to ensure that there are uninterrupted supplies of medical commodities and services. This requires scaling up the ability of local bodies to manage drug procurement and general logistics and adequate human resource in local healthcare centres. This article documents the efforts made so far in context of health sector federalization and synthesizes the progress and challenges to date and potential ways forward. This paper is written at a time while it is critical to review the federalism initiatives and develop way forward. As Nepal progress towards the federalized health system, we propose that the challenges inherent with the transition are critically analysed and mitigated while unfolding the potential of federal health system.